MODEL INTEGRATIF PSIKOLOGI PENDIDIKAN DALAM PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR: SUATU KAJIAN KONSEPTUAL - Nadiyah Zulfa; Hilmah; Eka nurwandari; Evi Ardiansyah; Tatu Maesaroh (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2025)
Character education at the elementary school level still faces conceptual challenges, especially related to the lack of integration between educational psychology principles and character building strategies. This study aims to develop an integrative model of educational psychology in character building of elementary school students. Using a qualitative approach with a conceptual-reflective study design, data were collected through a systematic literature study of educational psychology theories and character education models. Thematic content analysis was used to synthesize key concepts into a conceptual model. The results produced a model that combines developmental, self-regulation, and social learning theories with moral and social-emotional learning (SEL) approaches. The model emphasizes the role of teachers and the learning environment in supporting the internalization of character values. In conclusion, this integrative model offers a systematic and applicable framework to strengthen the effectiveness of character education in primary schools.